Pemanfaatan Perpustakaan Sekolah Sebagai Penunjang Kegiatan Belajar dalam Meningkatkan Hasil Belajar Ekonomi Peserta Didik Kelas X IIS pada SMAN-3 Palangka Raya - Anisa Sofyana; Sonedi Sonedi (Neraca: Jurnal Pendidikan Ekonomi, 2018)
This study aims to find out how the use of school libraries as supporting learning activities in improving economic learning outcomes. The method used in this research is qualitative methods and data collection techniques used in this study are observation, interviews, and documentation. The results of the school library research have been used by some students as well as visitors who come to read, find information, borrow books and use as a place to practice traditional music art is good enough. Students also feel comfortable when visiting the library because the condition of the room is good and clean, the books are arranged quite neatly. But the researchers found a lack of bookshelves because there are always new library materials and lack of chairs because they are often used for school purposes The book collection is quite complete, but the lack of interest of students in participating in visiting and utilizing the library. The researcher found a list of library visits and an increase in the list of economic subjects